A Prototype of Wireless Sensor Network Used In Precision Agriculture - Seth, Avalokita Anupam; Singh, Ritu (International Journal of Computer Sciences and Engineering, 2025)
A Wireless Sensor Network (WSN) consists of spatially distributed autonomous devices using sensors to monitor both environmental or physical conditions. In agriculture, WSNs are used for increasing the performance, high power efficiency and real time monitoring of environment. This paper proposes a real time system in which sensors are used and Arduino to monitor the temperature, humidity and soil moisture and hence presents the data to the users. We have also used solar sun tracker to increase the overall efficiency of the whole system. It uses Light Dependent Resistors (LDR) to sense the sunlight from the sun to convert it into voltage and generates electricity. This system can also be used in the remote areas.